Structural and magnetic properties of Zn doped magnetite nanoparticles obtained by wet chemical method - Sergio Ferrari (2015)
The structural and magnetic properties of Fe(3-x)ZnxO4(x: 0, 0.1, 0.2, 0.5, 1) nanoparticles, prepared by wet chemical method, have been studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), Mössbauer spectroscopy, and magnetization measurements. The nanoparticles are polyhedrical-shaped with a narrow distribution in size as it was verified by SEM. By Rietveld analysis of XRD patterns, it was determined that the crystallites' sizes of Fe(3-x)ZnxO4 in spinel structure is in the range of 30 to 50 nm. Hysteresis cycles, measured at different temperatures (300, 200, 100, 50, and 7 K), showed an increase in saturation, while temperature is diminished, as it is expected. All the samples, exhibited a high blocking temperature of ~350 K, as it was determined by zero field cooling-field cooling measurements. This fact, reveals their strongly interacting superparamagnetic nature. Real ac susceptibility increases with temperature, while the imaginary part has a maximum, which depends on frequency, and it is related to a critical temperature, which depends on composition. A Néel-Arrhenius dependence of frequency on the critical temperature was found for all the samples. We determined a minimum of the effective anisotropy for x=0.2.